探討授課研究對大學英語兼任教師教學之影響 Investigating the Influences of Lesson Study on College EFL Adjunct Faculty's Instruction - 李多耕 To-Ken Lee (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2021)
台灣大專院校中以英語為外語的教師們，在規劃課程和教學活動時，往往僅能獨力進行。特別是兼任教師，除了須獨力進行課程規畫外，相較於專任教師，所能獲取的專業成長機會，也相對稀缺。本研究利用授課研究模式，讓一組私立大學內，以英語為外語的兼任教師，形成教學社群，並探究這些教師參與者的教學如何增益。本研究設計採用質性 研究，研究資料來源涵蓋課堂觀察以及訪談紀錄。研究結果顯示，執行授課研究有助於促進教師間的專業合作、改善教學時的用字遣詞、以及型塑教師的學習社群。授課研究提供教師互惠學習的框架，讓教師們能在展示教學和評論觀課中，從其他教師成員身上，了解到自己教學的盲點。然而，本研究亦發現不利於執行授課研究的兩項因素，為教師 有限的時間和避免批判其他教師的展示教學。此兩點會導致授課研究對教師專業成長的效力，受到侷限。雖然授課研究廣受研究者注意，但相關研究目前僅限於國小和國中教師，而透過探討授課研究對大學英語兼任教師的影響，本研究旨在補足相關文獻於受測教師背景的侷限性。本研究結果發現，授課研究能提供大學兼任英語教師團體一系統化的循環程序，讓教師們能透過共同設計、示範教學、觀摩教學，以及改進示範教學等步驟，來提升教學效能。 College instructors of English as a Foreign Language (EFL) in Taiwan typically work alone when planning their teaching activities. In particular, adjunct instructors work isolated during class planning and teaching, and have fewer opportunities for professional development than fulltime instructors. This study attempts to propose a model for collaborative lesson study group for EFL adjunct instructors in a private college in Taiwan and investigates how the practices of these teacher participants can be advanced. Data collection in this study consists of qualitative inquiries, classroom observations and interview transcripts. The results indicate that the execution of a collaborative lesson study group of college adjunct faculties enhance teachers’ collaboration, improve instructional wording, and forge a teachers’ learning community. A collaborative study group for lesson construction helps to build a reciprocal model of learning, where teachers can help each other to identify their instructional weakness or learn from members’ comments regarding demonstration lessons. However, teachers aware that to critique and question demonstration instructor might get on the nerves within group and limited common time for college adjunct faculties could diminish the effectiveness of lesson study group. Even the study of lesson construction has gained research attention, investigations of the targeted participants are so far limited to elementary and secondary school teachers. This study aims to fill the gap of previous researches regarding collaborative lesson study groups by exploring its influence on EFL adjunct faculties. The results reveal that a lesson construction study group provides EFL adjunct faculty members a systematic cycle that allows a group of teachers to streamline instructions and teaching activities through collaborative design, teaching activities design, classroom observations, and then to collaboratively refine their class lessons.